Miniaturized CPW-Fed Triband Antenna with Asymmetric Ring for WLAN/WiMAX Applications - Shanshan Huang; Jun Li; Jianzhong Zhao (Journal of Computer Networks and Communications)
A compact CPW-fed triband slot antenna for WLAN/WiMAX applications is proposed. The proposed antenna is formed by an asymmetric ring, an inverted L-strip, and a straight strip. By employing these structures, the antenna can generate three operation bands with compact size and simple structure. The measured and simulated results show the presented antenna has impedance bandwidths of 100 MHz (2.39–2.49 GHz), 360 MHz (3.36–3.72 GHz), and 760 MHz (5.13–5.89 GHz), which covers both WLAN in the 2.4/5.2 GHz bands and WiMAX in the 3.5/5.5 GHz bands. The antenna is successfully simulated and measured, showing triple bands can be obtained by using three different radiators and also indicating that the proposed antenna is suitable for the WiMAX/WLAN applications.